Eileen Gray and the design of Sapphic modernity: Staying in - Rault, Jasmine (Ashgate, 2011)
The first book-length feminist analysis of Eileen Gray's work, Eileen Gray and the Design of Sapphic Modernity: Staying In argues that Gray's unusual architecture and design - as well as its history of abuse and neglect - emerged from her involvement with cultures of sapphic modernism. Bringing together a range of theoretical and historical sources, from architecture and design, communication and media, to gender and sexuality studies, Jasmine Rault shows that Gray shared with many of her female contemporaries a commitment to designing spaces for sexually dissident modernity. This volume examines Gray's early lacquer work and Romaine Brooks' earliest nude paintings; Gray's first built house, E.1027, in relation to Radclyffe Hall and her novel The Well of Loneliness; and Gray's private house, Tempe Ã Pailla, with Djuna Barnes' Nightwood. While both female sexual dissidence and modernist architecture were reduced to rigid identities through mass media, women such as Gray, Brooks, Hall and Barnes resisted the clarity of such identities with opaque, non-communicative aesthetics. Rault demonstrates that by defying the modern imperative to publicity, clarity and identity, Gray helped design a sapphic modernity that cultivated the dynamism of uncertain bodies and unfixed pleasures, which depended on staying in rather than coming out.
Keywords: architecture; design; discipline; europe; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; royaume-uni; régions géographiques; sexualité; thématiques

Critical geographies and the uses of sexuality: deconstructing queer space - Oswin, Natalie (Progress in Human Geography, 2008)
Scholarship on queer geographies has called attention to the active production of space as heterosexualized and has levelled powerful critiques at the implicit heterosexual bias of much geographical theorizing. As a result, critical geographers have begun to remark upon the resistance of gays, lesbians and other sexual subjects to a dominant heterosexuality. But such a liberal framework of oppression and resistance is precisely the sort of mapping that poststructuralist queer theory emerged to write against. So, rather than charting the progress of queer geographies, this article offers a critical reading of the deployment of the notion of `queer space' in geography and highlights an alternative queer approach that is inseparable from feminist, materialist, postcolonial and critical race theories.
Keywords: LGBTQIA2+; approches et analyses; architecture; cours; discipline; espace; géographie; hétéronormativité; premier cycle; queer; résistance; sciences humaines; soc2014; thématiques